2011
DOI: 10.1590/s1516-35982011000100017
|View full text |Cite
|
Sign up to set email alerts
|

Relative expression of mRNAs related to cavitation process in bovine embryos produced in vivo and in vitro

Abstract: -The objectives of this work were to identify and to evaluate possible differences on gene expression of aquaporins and Na/K-ATPases transcripts between embryos in vivo and in vitro produced. For each group, 15 blastocysts distributed in three pools were used for RNA extraction followed by amplification and reverse transcription. The resulting cDNAs were submitted to Real-Time PCR, using the GAPDH gene as endogenous control. It was not possible to identify AQP1 transcripts. Relative expression of AQP3 (1.33 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been observed that the embryos produced in vivo are of high quality and less apoptosis than those produced in vitro (Pomar et al, 2005;Melka et al, 2010), and the major reason that might contribute to depress oocyte and embryo competence is the in vitro conditions (Wohlres-Viana et al, 2011). In this study, we have used different concentrations of SFF in an attempt to optimize the in vitro conditions of oocyte maturation to be closer to the in vivo status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the embryos produced in vivo are of high quality and less apoptosis than those produced in vitro (Pomar et al, 2005;Melka et al, 2010), and the major reason that might contribute to depress oocyte and embryo competence is the in vitro conditions (Wohlres-Viana et al, 2011). In this study, we have used different concentrations of SFF in an attempt to optimize the in vitro conditions of oocyte maturation to be closer to the in vivo status.…”
Section: Discussionmentioning
confidence: 99%